Biosensing Detection of the SARS-CoV-2 D614G Mutation. Issue 4 (April 2021) - Zhang, Yang; Xi, Hui; Juhas, Mario
Abstract : The emergence of a mutant strain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with an amino acid change from aspartate to a glycine residue at position 614 (D614G) has been reported and this mutant appears to be now dominant in the pandemic. Efficient detection of the SARS-CoV-2 D614G mutant by biosensing technologies is therefore crucial for the control of the pandemic.